Cassia alata Seed Extract Loaded Chitosan: Synthesis and Release Study - Kartha, Vidya G.; Suryavanshi, Vandana; Maharana, Tungabidya (Asian Journal of Chemistry, 2019)
In present study, a herbal extract, Cassia alata seed extract has been loaded into chitosan matrix as drug delivery systems. The major components of Cassia alata seed extract are flavonoids and anthraquinone. Cassia alata seed extract loaded chitosan has been characterized by FTIR, SEM, XRD, thermal and NMR analysis. The characterization has shown successful loading of Cassia alata seed extract into chitosan. Further, swelling properties and drug release profiles of Cassia alata seed extract loaded chitosan has been carried out at two different pH 2 and 7.4. It is observed that the swelling behaviour and drug release profile was much better at pH 2 than pH 7.4. Thus, the loaded chitosan can be used as a biomedicine.